Development of Eco Print on Leather Craft Products to Increase Production of Faro Leathercraft Artisans - Muh Fakhrihun Naam; Wulansari Prasetyaningtyas; Taofan Ali Achmadi; Dewi Mustikaningtyas; Nanda Delva Fitriyah; Fatimah Azzahra (Jurnal Abdimas, 2024)
Community service focused on product creation and development, exceptionally functional leather craft products such as shoes, wallets, and bags, holds great promise. Integrating eco-print motif creation within these leather crafts is strategically significant. It enhances the production of these crafts and contributes positively to the economy of Faro Leather Craft artisans in the Bumirejo Mungkid Magelang foster village. One of the main challenges the artisans face is the lack of potential for creating new, varied, and dynamic motifs, especially considering their beginner level of expertise in leather craft creation. Therefore, there is a need for innovations that are easy to implement. The solution proposed through this community service involves mass production of leather crafts using eco-print techniques, thereby increasing production. This approach also involves applying and utilizing science and technology for the benefit of Magelang village, positioning it as a foster partner of Unnes. It aims to provide new insights into creating motifs with environmentally friendly innovative tools. Additionally, this innovation is targeted at artisans, including the younger generation, to foster a love for batik while focusing on the regeneration and development of batik in the Bumirejo Mungkid Magelang village. To achieve these goals, the community service project involves creating eco prints on leather craft products for use by artisans, artists, and new entrepreneurs. The initiative includes both new and existing artisans interested in participating as tenants. The project activities encompass execution, material exploration, form experimentation, and motif understanding. This includes the creation and motif development process using eco-print techniques, data analysis, motif creation, copyright registration, and report compilation. The outputs of this community service include products from training sessions, scientific articles, copyrights, and reports. Additional outputs involve consumer feasibility testing, exhibitions, and mandatory outputs such as scientific articles, highlight videos, copyrights, and reports.